Student-on-staff violence at South African universities: A qualitative study - Bonginkosi Hardy MUTONGOZA (GIornale Italiano di Psicologia e Medicina del Lavoro)
Introduction: Although universities have traditionally been regarded as ivory towers that are safe spaces for learning and personal development, recent trends in South Africa have revealed that universities are increasingly becoming recognized as sites for violence, including student-on-staff violence. Against this background, this study sought to explore narratives of student-on-staff violence and determine the extent to which these incidents happened. Methods: Using a qualitative approach, the study employed a phenomenological research design. Participants were selected using purposive sampling, and data were collected using semi-structured interviews with 32 students and four staff at three public universities. Data was analyzed thematically. Results: The findings revealed that student-on-staff violence often took the form of protest-related violence, verbal abuse, and physical assault of staff members. The study found that these acts of violence essentially responded to perceived systemic abuses and authoritarian governance within selected South African higher education. While some reported instances of violence were retaliatory, there are also cases of unprovoked violence by students on staff, including incidents such as drunken assaults on campus security personnel and disruptions of lectures on online platforms. Discussion: The consequences of student-on-staff violence were found to extend beyond immediate harm and damage, including feelings of insecurity and anxiety among lecturers and support personnel, ultimately impeding university teaching and learning experiences. Such violence undermined the fundamental principles of academic institutions and created a hostile and unsafe environment for stakeholders.